Análisis, diseño e implementación de un sistema interactivo para el control y administración de inventario de equipos para el laboratorio de redes y telecomunicaciones de la Escuela de Informática de la Facultad de Ingeniería Civil de la Universidad Técnica de Machala - Benites Suquitana, Jorge Luis (2014)
The laboratory network and Communications School of Informatics at the Technical University of Machala, does not have a computer system that controls and manages the information of entry, exit and loans of equipment you own, normally performed manually causing delays.